The mediating role of cognitive workload and loneliness in the relationship between internet addiction and sleep quality among public university students in Malaysia - Ma’rof, Aini Azeqa; Abdullah, Haslinda; Rosnon, Mohd Roslan (Human Resources Management Academic Research Society (HRMARS), 2024)
This study investigates the mediating roles of cognitive workload and loneliness in the relationship between internet addiction and sleep quality among public university students in Malaysia. Utilizing a cross-sectional survey of 425 students from various institutions in Klang Valley, the research employs established instruments to measure internet addiction, cognitive workload, loneliness, and sleep quality. The findings reveal that internet addiction significantly predicts poor sleep quality, with cognitive workload and loneliness serving as crucial mediators. Students with higher levels of internet addiction experience greater cognitive workload and loneliness, which in turn, adversely affect their sleep quality. These results underscore the importance of addressing both cognitive demands and social factors in interventions aimed at improving sleep health among university students. Practical strategies suggested include implementing cognitive workload management programs, promoting healthy internet use, and fostering social connections. This study provides empirical evidence on the mediating roles of cognitive workload and loneliness in the relationship between internet addiction and sleep quality. By understanding these dynamics, educators and mental health professionals can develop targeted strategies to support students in managing internet addiction and improving sleep quality, ultimately enhancing their overall wellbeing. These findings offer valuable insights for both academics and practitioners in the fields of mental health and educational intervention.